Demonstration of bioplastic production from CO2 and formate using the reductive glycine pathway in E. coli - Daria Fedorova; Roee Ben-Nissan; Eliya Milshtein; Cassandra Reyes; Ghil Jona; Nili Dezorella; Gil Feiguelman; Rostislav Fedorov; Aya Gomaa; Ariel B. Lindner; Elad Noor; Ron Milo (PLoS ONE, 2025)
There is a strong need to develop technologies that reduce anthropogenic pollution and the dependence on nonrenewable Earth resources. One way of doing so is by harnessing biological systems for replacing the production of fossil-fuel based goods with low-environmental-impact alternatives. Recently, progress was made in engineering the model organism E. coli to grow using CO2 and formate as its only carbon and energy sources using the reductive glycine pathway (rGlyP). Here, we use this engineered strain of E. coli as a host system for the production of polyhydroxybutyrate (PHB), a biologically derived and biodegradable plastic. The production of PHB in this strain was confirmed using Nile red fluorescence microscopy, transmission electron microscopy, and HPLC analysis, with a yield of 0.172 ± 0.005 mg/L of PHB after 120 hours of incubation. Since formate can be efficiently generated from CO2 by electrochemical reduction using renewable energy sources, this study serves as a proof of concept for the emerging field of electro-bioproduction.